Alelopatia e citogenotoxidade de extratos de diferentes estruturas de Garcinia brasiliensis Mart. (Clusiaceae) em bioensaio com Lactuca sativa L. - Barroso, Ênnio Miranda (2014)
With the changing needs of agriculture nowadays the use of synthetic herbicides has become indispensable to obtain high productivity and rid the crops from pests and weeds. The potential for the use of natural plant products, as herbicides is large, particularly in agriculture agroecological, either for direct use or as the basis for the synthesis of new herbicidal molecules, since although chemical control method is practical, has a number of limitations. Therefore, the objective of the study was to evaluate the effects of extracts of leaf, pericarp and seed Bacupari in bioassays using Lettuce (Lactuca sativa L.) as a target plant, trying to understand the action of allelochemicals and expand the set of information about the action phytotoxic extracts of this plant. The bioassays with cypselae Lettuce were conducted in a germination chamber BOD at 25 ± 2°C, 12 h photoperiod for 96 h with aqueous and ethanolic leaf extracts of leaf, pericarp and seed in different concentrations, being used as a control distilled water. Tests for germination (G), germination speed index (GSI) and mitotic index (MI) were made ​​with four replicates of 30 seeds Lettuce each exposed to different treatments. The root tips were collected, fixed in Carnoy and stored until the making of cytological preparations in which 3000 cells were counted per treatment for evaluation of mitotic index (MI), besides the evaluation of chromosomal abnormalities. A second experiment was conducted using the same treatments to examine the phytotoxicity of Bacupari taking as variables the length of 10 roots of each repetition and the fresh and dry biomass of seedlings obtained after 96 hours of culture. The aqueous and ethanolic leaf extracts of pericarp showed reducing effect germination, initial growth, the mitotic index and an increased rate of chromosomal abnormalities, the seeds of Lettuce, concentration dependent, exerting phytotoxic and cytotoxic action on the bioassay. However, the same was not observed for the data of the ethanol extract of leaf and seed, which acted only on the initial growth and inhibition of mitotic index, featuring a cytotoxic action of bioactive compounds present in this extract.